Correction.
To understand the recall some theory.
Equation of the form "f(p,q)=0" i.e. the equation contains "p" and "q" only.
Suppose that "z(x,y)=ax+by+c" is solution of equation, then
"p=\\frac{\\partial z}{\\partial x}=a\\,\\,\\,\\text{and}\\,\\,\\,q=\\frac{\\partial z}{\\partial y}=b"
substitute the above in equation "f(p,q)=0" , we get "f(a,b)=0" on solving this we can get "b=\\phi(a)" , where "\\phi" is known function. Using "b=\\phi(a)" , the complete solution of the given partial equation is
"z=ax+\\phi(a)y+c" In our case,
"p^2-q^2=4\\longrightarrow\\underbrace{ p^2-q^2-4}_{f(p,q)}=0"
Then, suppose
"z=ax+by+c\\\\[0.3cm]\np=\\frac{\\partial z}{\\partial x}=a\\,\\,\\,\\text{and}\\,\\,\\,q=\\frac{\\partial z}{\\partial y}=b\\\\[0.3cm]\np^2-q^2-4=0\\longrightarrow a^2-b^2-4=0\\longrightarrow\\\\[0.3cm]\n\\boxed{b=\\pm\\sqrt{a^2-4},\\,\\,\\,\\forall |a|\\ge2}"
Conclusion,
"\\boxed{z=ax\\pm\\sqrt{a^2-4}\\cdot y+c\\,\\,\\,-\\,\\,\\text{is the general integral}}"
and
"z=ax+\\sqrt{a^2-4}\\cdot y+c"
is the complete integral as a special case.
Comments
Leave a comment